Responsible Digital Transformation For A Sustainable Society - Sachdeva, Timcy; Sharma, Ridhima (LPPM Universitas Duta Bangsa Surakarta, 2024)
Digital transformation represents a profound shift in how technologies are integrated into society, reshaping economic, social, and environmental landscapes. This paper explores the concept of responsible digital transformation, emphasizing the need for integrating ethical practices, environmental sustainability, and social equity into the digital innovation process. By examining the impacts of digital technologies, the paper outlines challenges and proposes strategies for ensuring that digital transformation contributes positively to a sustainable society. Through a comprehensive review of current literature and case studies, the research highlights the role of stakeholders, governance frameworks, and emerging trends in promoting responsible digital practices.